VIGOUR OF MAIZE SEEDS PRODUCED AT THE MAIZE RESEARCH INSTITUTE, ZEMUN POLJE - D. Lazarević, Tijana; D. Petrović, Tanja; N. Todorović, Goran; D. Sečanski, Mile; Golijan-Pantović, Jelena; S. Lekić, Slavoljub (Journal of Agricultural Sciences (Belgrade), 2024)
Maize is one of the economically most important crops. Its immense significance arises from its various uses, high yielding and the production scope. In order to establish a lucrative production, first-rate seeds are required. Therefore, the aim of this study was to test vigour of maize seeds conventionally and organically produced. The seeds of maize variety Rumenka were used and tested at the Maize Research Institute, Zemun Polje in its Seed Testing Laboratory. According to results, it can be concluded that although there was a minimal difference in the percents of first count of germinated seeds between the two types of seeds, total germination was equal (98%). The results of the germination test performed after seed accelerated ageing indicate that total seed germination was higher in organic than in conventional seeds (39% vs. 33%). The electric conductivity of leachate per gram of weight of conventional maize seeds was 4.90 µS/cmg and of organic maize seeds was 3.66 µS/cmg on average. According to stated values it can be concluded that maize seeds of both types of production are characterised by high viability and are suitable for earlier sowing under unfavourable environmental conditions. According to results, the radicle emergence was uniform amounting to 84% in conventional seeds and to 85% in organic seeds.